Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) = 17/19 - 17/19 + 27/35 + 35/35 = 0 + 62/35
b) = 1/3 x 4/5 + 1/3 x6/5 + 1/3 x 2 = 1/3(4/5 + 6/5 + 2) = 1/3 x 4 = = 4/3
c) 4/7 x 2/9 + 4/7 x 7/9 + 2/3 = 4/7 x (2/9 + 7/9) + 2/3 = 4/7 x 1 + 2/3 = 26/21
A) 17/19 - 17/19 + 27/35 + 35/35 = 0 + 62/35
B) 1/3 x 4/5 + 1/3 x 6/5 + 1/3 x 2 = 1/3 x(4/5 + 6/5 x 2 ) = 1/3 x 4 = 4/3
c) TƯƠNG TỰ CÂU A VÀ B
* HOKTOT*
NHA
a) \(3\left(2-x\right)+5\left(x-6\right)=98\)
\(\Rightarrow6-3x+5x-30=98\)
\(\Rightarrow\left(6-30\right)+\left(-3x+5x\right)=98\)
\(\Rightarrow-24+2x=98\)
\(\Rightarrow2x=98-\left(-24\right)\)
\(\Rightarrow2x=122\)
\(\Rightarrow x=122:2\)
\(\Rightarrow x=61\)
Vậy x = 61
b) \(3x-2=2x-3\)
\(\Rightarrow3x-2x=2-3\)
\(\Rightarrow x=-1\)
Vậy x = -1
c) \(\left(x-7\right)\left(x^3-8\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-7=0\\x^3-8=0\end{cases}}\Rightarrow\orbr{\begin{cases}x-7=0\\x^3=8\end{cases}}\Rightarrow\orbr{\begin{cases}x=7\\x=2\end{cases}}\)
Vậy x = 7 hoặc x = 2
_Chúc bạn học tốt_
a.6-3X+5X-30=98
2X-24=98
2X=74
X=37
b.3X-2X=2-3
X=-1
c.X-7=0 X=7
X^3-8=0 X=2
1, 2x - 35 = 15
2x = 15 + 35
2x = 50
x = 50 : 2
x = 25.
2, 3x + 18 = 12
3x = 12 - 18
3x = -6
x = -6 : 3
x = -2.
3, / x - 1 / = 0
=> x \(\in\varnothing\).
4, -13 /x/ = - 26
/x/ = -26 : -13
=> \(\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)
Vậy x \(\in\){ 2 ; -2}.
5,4 - ( 27 - 3 ) = x - ( 13 - 4 )
4 - 24 = x - 9
-20 = x - 9
-x = 9 + 20
-x = 29
x = -29.
6, 47 - ( x + 15 ) = 21
47 - x - 15 = 21
-x - 15 = 21 - 47
-x - 15 = -26
-x = -26 + 15
-x = - 11
x = 11.
7, -5 -( 24 - x) = - 11
-5 - 24 + x = -11
-24 + x = -11 + 5
-24 + x = -6
x = -6 + 24
x = 18.
8, 6 - /x/ = 2
/x/ = 6 - 2
\(\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
Vậy x \(\in\left\{3;-3\right\}.\)
9, 6 + /x/ = 2
/x/ = 2 - 6
=> x = -4.
2x - 35 = 15
=> 2x = 15 + 35
=> x = 50 : 2
=> x = 25
3x + 18 = 12
=> 3x = 12 - 18
=> x = ( -6 ) : 3
=> x = -2
| x - 1 | = 0
=> x - 1 = 0
=> x = 0 + 1
=> x = 1
-13 * | x | = -26
=> | x | = -26 : ( -13 )
=> | x | = 2
32,2857 và 12,8 và -498814315,3 và 0,1 và 11
tổng = - 498814259,1
1) 5(x - 2) + 27 = 4x - 8
=> 5x - 10 + 27 = 4x - 8
=> 5x + 17 = 4x - 8
=> 5x - 4x = -8 - 17
=> x = -25
2) 3(x + 1) + 2(x + 2) = -13
=> 3x + 3 + 2x + 4 = -13
=> 5x + 7 = -13
=> 5x = -13 - 7
=> 5x = -20
=> x = -20 : 5
=> x = -4
3) (2x + 4)(5 - x) = 0
=> \(\orbr{\begin{cases}2x+4=0\\5-x=0\end{cases}}\)
=> \(\orbr{\begin{cases}2x=-4\\x=5\end{cases}}\)
=> \(\orbr{\begin{cases}x=-2\\x=5\end{cases}}\)
Vậy ...
4) x2 - 3x = 0
=> x(x - 3) = 0
=> \(\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
Vậy ...
5) x2 - 3x + 2 = 0
=> x(x - 3) = -2
=> x(x - 3) = 1 . (1 - 3)
=> x = 1
a ) 10 x X - 1 - 3 - 5 - 7 - ... - 19 = 2 + 4 + 6 + ... + 20
10 x X - 1 - 3 - 5 - 7 - ... - 19 = 110
10 x X - ( 1 + 3 + 5 + 7 + ... + 19 ) = 110
10 x X - 100 = 110
10 x X = 110 + 100
10 x X = 210
X = 210 : 10
X = 21